2016
DOI: 10.18632/oncotarget.10777
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation by memantine in therapy of Alzheimer's disease is mediated through inhibition of Kv1.3 channels and T cell responsiveness

Abstract: Memantine is approved for the treatment of advanced Alzheimer's disease (AD) and reduces glutamate-mediated neuronal excitotoxicity by antagonism of N-methyl-D-aspartate receptors. In the pathophysiology of AD immune responses deviate and infectious side effects are observed during memantine therapy. However, the particular effects of memantine on human T lymphocytes are unresolved. Here, we provide evidence that memantine blocks Kv1.3 potassium channels, inhibits CD3-antibody- and alloantigen-induced prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…We reported that in lymphocytes memantine blocks K v 1.3 channel activity and diminishes lymphocyte effector function [37, 38]. Furthermore, standard doses of memantine applied in Alzheimer therapy inhibit K v 1.3 channels on patients’ peripheral blood T cells and alter T cell reactivity in vivo [39]. Thus, we asked whether pharmacological inhibition of K v 1.3 channels by memantine could be an option to enhance cell death of acute leukemia cells induced by the chemotherapeutic drug cytarabine (AraC).…”
Section: Introductionmentioning
confidence: 99%
“…We reported that in lymphocytes memantine blocks K v 1.3 channel activity and diminishes lymphocyte effector function [37, 38]. Furthermore, standard doses of memantine applied in Alzheimer therapy inhibit K v 1.3 channels on patients’ peripheral blood T cells and alter T cell reactivity in vivo [39]. Thus, we asked whether pharmacological inhibition of K v 1.3 channels by memantine could be an option to enhance cell death of acute leukemia cells induced by the chemotherapeutic drug cytarabine (AraC).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, administration of memantine leads to a significant reduction of memory T cells (e.g., CD45RO+ CD4+) in the blood. This could be a double-edged sword as memantine can control unbalanced CD4+ T cells infiltration in AD, but may also increase the infection rate [ 75 ] Memantine can selectively inhibit Th1 but not Th2 or Treg [ 37 , 76 ] ( Figure 5 and Table 7 ). However, its effect on Th17 is still not known.…”
Section: Effect Of Ad Drugs On Cd4+ T Cells Proliferation and Diffmentioning
confidence: 99%
“…CD45RO+ CD4+ ) in the blood. This could be a double edge sword as memantine can control unbalanced CD4+ T cells infiltration in AD, but may also increase the infection rate [38]. Regrettably, the information covering the difference in the impact of these drugs on CD4+ T cells subpopulations homing is scarce, however vital that could be.…”
Section: Main Text I)mentioning
confidence: 99%